Prevalence of Mycoplasma hominis and Ureaplasma urealyticum (T strains) in urine of adolescents. - Foy, H (1975)
Adolescent children were surveyed for colonization with Mycoplasma hominis and Ureaplasma urealyticum by culturing urine specimens. Rates were compared between three study groups: (i) 397 children attending parochial schools, (ii) 293 children attending an adolescent clinic specializing in adjustment problems, and (iii) 86 children attending a renal clinic. The recovery rate was higher among postpubertal girls attending the renal clinic (33%) and the adolescent clinic (26%) than among students attending parochial high school (males 2%, females 8%). Girls had approximately eightfold higher rates than boys of the same age. Isolation of Mycoplasmataceae was associated with certain sociological determinants, such as dating, cigarette smoking, and coming from a broken home, but also with abnormal findings (protein, leucocytes) in urine.